Comparative study of PCR test kits for ASFV DNA detection - M. S. Krasnikova; S. P. Yatsentyuk; M. B. Bryusova; A. D. Kozlova; М. А. Gergel (Ветеринария сегодня)
The paper presents comparative test results of 12 domestically produced diagnostic kits/PCR test systems for DNA detection of the African swine fever virus with regard to the following parameters: completeness and correctness of instructions for use; labeling and package contents; convenience of using the kit; shelf life stability of reagents; stability of reagents after transportation and repeated freezing – thawing; batch-to-batch repeatability; sensitivity of various test materials and specificity of kits. The study of the instructions for use and kit contents revealed incompleteness of some instructions. It was noted that some manufacturers make serious errors in the instructions, which can significantly affect the interpretation of test results. It was also observed that there is insufficient control of the manufacturing process, which results in the production of faulty kits, as well as kits with poor-quality components and errors in the labeling. Thus, during the study, one kit showed its inactivity, demonstrating the absence of accumulation curves of the fluorescent signal during amplification of both positive controls and DNA of ASFV isolates. When the specificity was assessed, all the kits showed absence of non-specific reactions and acceptable sensitivity when testing various types of ASFV-containing material (blood, suspensions of pork spleen and pork casings used in sausage production). The stability test showed a sharp deterioration in the quality of operation of one kit within the shelf life period, and a significant decrease in the fluorescence signal was detected during repeated freeze – thaw cycles for another kit. Comparison of the repeatability results of different kit batches of the same manufacturer showed significant discrepancies for 41.5% of all kits. It was found that only 33% of the studied kits for ASFV DNA detection were compliant. The results of this study demonstrate the need for control of the manufactured diagnostic kits used in state programs for animal disease monitoring.